Secondary casting material for aluminum piston combustion chamber and preparation method thereof
By using secondary casting materials used in the aluminum alloy piston combustion chamber with aluminum powder and Fe-Cr-B matrix alloy, a stable reinforced phase is formed, which solves the problems of elemental diffusion and segregation under high temperature and high pressure, and improves the strength and fatigue resistance of the material.
Patent Information
- Application Number
- CN202310578157.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-05-22
AI Technical Summary
The aluminum alloy piston combustion chamber is prone to elemental diffusion and segregation under high temperature and high pressure, resulting in a decrease in tensile strength and fatigue resistance.
Aluminum powder and Fe-Cr-B matrix alloy are used as the matrix of secondary casting materials to form reinforced phases such as FeAl, CrAl and FeB at high temperatures, combining silicon carbide, copper powder, magnesium powder and nickel powder to improve the stability of the reinforced phase and prevent segregation.
The strength and fatigue resistance of the secondary casting material are improved, the tensile strength and fatigue resistance are enhanced, and cracks are prevented under high temperature and high pressure.
Smart Images

Figure BDA0004240722180000071 
Figure BDA0004240722180000081 
Figure BDA0004240722180000082
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of piston manufacturing, and in particular to a secondary casting material and a preparation method for an aluminum piston combustion chamber. Background Art
[0002] Material aging of the piston combustion chamber is usually caused by high temperature and high pressure. During the operation of the internal combustion engine, the fuel gas burns rapidly in the combustion chamber, causing the temperature and pressure in the combustion chamber to rise rapidly.
[0003] Aluminum alloy is a material commonly used to make piston combustion chambers. In order to facilitate mass production and improve the performance of aluminum alloy, most manufacturers increase the content of elements such as nickel and copper in the alloy. However, under high temperature and high pressure, elements such as aluminum, copper and nickel are prone to diffusion, leading to the occurrence of segregation, which in turn reduces the tensile strength and fatigue resistance of the alloy. Summary of the invention
[0004] In order to solve the above technical problems, a secondary casting material for an aluminum piston combustion chamber is developed. The present application provides a secondary casting material for an aluminum piston combustion chamber and a preparation method thereof.
[0005] On the one hand, the secondary casting material for the aluminum piston combustion chamber provided in the present application includes the following components by weight: 0.5-1.5 parts of silicon carbide, 40-70 parts of aluminum powder; 10-15 parts of Fe-Cr-B matrix alloy, 4-8 parts of copper powder; 0.1-0.8 parts of magnesium powder and 1-3 parts of nickel powder.
[0006] By adopting the above technical scheme, aluminum powder and Fe-Cr-B matrix alloy are used in combination as the matrix of the secondary casting material. Under high temperature treatment, strengthening phases such as FeAl, CrAl and FeB are formed. The atomic arrangement structure and lattice size, composition and compatibility inside the strengthening phase are relatively stable, which can reduce the probability of element segregation in the alloy and improve the strength and fatigue resistance of the secondary casting material. At the same time, silicon carbide can inhibit the diffusion rate of each component at high temperature. Therefore, in combination with copper powder, magnesium powder and nickel powder, the stability of the strengthening phase can be further improved, the phenomenon of segregation under high temperature and high pressure can be prevented, and the occurrence of cracks can be prevented, thereby further improving the tensile strength and fatigue resistance of the secondary casting material.
[0007] As an improvement of the above technical solution, the mass ratio of the aluminum powder to the Fe-Cr-B matrix alloy is (4.5-6.5):(1.2-1.4).
[0008] By adopting the above technical solution, the Fe-Cr-B matrix alloy and aluminum powder are matched in a specific ratio and addition amount, so that the components can play a more superior synergistic function, so that the Cr and B elements on the surface of the Fe-Cr-B matrix alloy can form a stronger interface bond with Al203, thereby further improving the strength and fatigue resistance of the secondary casting material.
[0009] As an improvement of the above technical solution, the secondary casting material also includes boron nitride, and the mass ratio of silicon carbide to boron nitride is (0.7-1.2):(0.3-0.5).
[0010] By adopting the above technical solution, silicon carbide-boron nitride adopts a specific ratio and addition amount, which can form a thin film on the surface of the mixed metal powder to prevent the metal powder from oxidation, so that the metal powders are fully dispersed and easy to mix evenly. At the same time, under the action of high temperature, the interface bonding force between aluminum powder and other metal powders can be strengthened, the diffusion rate of each component at high temperature can be suppressed, and the matrix becomes stronger, thereby effectively preventing the segregation phenomenon in the secondary casting material, thereby improving the tensile strength and fatigue resistance.
[0011] As an improvement of the above technical solution, the particle size of the silicon carbide is 20 to 60 μm.
[0012] As an improvement of the above technical solution, the hardness of the Fe-Cr-B matrix alloy is 52-62HRC.
[0013] As an improvement of the above technical solution, the purity of the Al, Mg, Ni and Cu metal powders is greater than 98%, and the particle size is 30-50 μm.
[0014] In a second aspect, the present application provides a method for preparing a secondary casting material for an aluminum piston combustion chamber, comprising the following steps:
[0015] S1, ball-milling the Fe-Cr-B matrix alloy particles to form powder;
[0016] S2. According to the formula, silicon carbide, Fe-Cr-B matrix alloy powder, aluminum powder, copper powder, magnesium powder and nickel powder are weighed respectively, mechanically stirred and mixed, and ultrasonically dispersed after mixing to obtain a mixed material;
[0017] S3, smelting the mixed material at 900-1200° C. to obtain alloy liquid for secondary casting.
[0018] As an improvement of the above technical solution, the heating rate in step S3 is 5-8°C / min
[0019] As an improvement of the above technical solution, the ball milling speed is 400r / min to 500r / min, and the ball milling time is 5 to 10h.
[0020] As an improvement of the above technical solution, the ultrasonic treatment time is 20-30 minutes.
[0021] In summary, the present invention includes at least one of the following beneficial technical effects:
[0022] 1. The present application uses aluminum powder and Fe-Cr-B matrix alloy in combination as the matrix of the secondary casting material. Under high temperature treatment, strengthening phases such as FeAl, CrAl and FeB are formed. The atomic arrangement structure and lattice size, composition and compatibility within the strengthening phase are relatively stable, which can reduce the probability of element segregation in the alloy and improve the strength and fatigue resistance of the secondary casting material. At the same time, silicon carbide can inhibit the diffusion rate of each component. Therefore, in combination with copper powder, magnesium powder and nickel powder, the stability of the strengthening phase can be further improved, and the phenomenon of segregation under high temperature and high pressure can be prevented, and cracks can be prevented, thereby further improving the tensile strength and fatigue resistance of the secondary casting material.
[0023] 2. The Fe-Cr-B matrix alloy and aluminum powder of the present application adopt a specific ratio and addition amount, so that the components can play a more superior synergistic function, so that the Cr and B elements on the surface of the Fe-Cr-B matrix alloy can form a stronger interface bond with Al203, thereby further improving the strength and fatigue resistance of the secondary casting material.
[0024] 3. The preparation method of the present application has a simple preparation process and can evenly disperse the aluminum powder-Fe-Cr-B matrix alloy system, so that the secondary casting material has a high degree of dispersion, thereby improving the bonding force between the components, thereby improving the tensile strength and fatigue resistance of the secondary casting material. DETAILED DESCRIPTION
[0025] The present application is further described in detail below in conjunction with embodiments.
[0026] The present application designs a secondary casting material for an aluminum piston combustion chamber, comprising the following components by weight: 0.5-1.5 parts of silicon carbide, 40-70 parts of aluminum powder; 10-15 parts of Fe-Cr-B matrix alloy, 4-8 parts of copper powder; 0.1-0.8 parts of magnesium powder and 1-3 parts of nickel powder.
[0027] The mass ratio of the aluminum powder to the Fe-Cr-B matrix alloy is (4.5-6.5):(1.2-1.4).
[0028] The secondary casting material also includes boron nitride, and the mass ratio of silicon carbide to boron nitride is (0.7-1.2):(0.3-0.5).
[0029] In a second aspect, the present application provides a method for preparing a secondary casting material for an aluminum piston combustion chamber, comprising the following steps:
[0030] S1, ball-milling the Fe-Cr-B matrix alloy particles to form powder;
[0031] S2. According to the formula, silicon carbide, Fe-Cr-B matrix alloy powder, aluminum powder, copper powder, magnesium powder and nickel powder are weighed respectively, mechanically stirred and mixed, and ultrasonically dispersed after mixing to obtain a mixed material;
[0032] S3. Smelting the mixed material at 900-1200° C. to obtain alloy liquid for secondary pouring.
[0033] The present application uses aluminum powder and Fe-Cr-B matrix alloy in combination as the matrix of the secondary casting material. Under high temperature treatment, strengthening phases such as FeAl, CrAl and FeB are formed. The atomic arrangement structure and lattice size, composition and compatibility inside the strengthening phase are relatively stable, which can reduce the probability of element segregation in the alloy and improve the strength and fatigue resistance of the secondary casting material. At the same time, under high temperature, silicon carbide can inhibit the diffusion rate of each component. Therefore, in combination with copper powder, magnesium powder and nickel powder, the stability of the strengthening phase can be further improved, and the phenomenon of segregation under high temperature and high pressure can be prevented, and cracks can be prevented, thereby further improving the tensile strength and fatigue resistance of the secondary casting material.
[0034] Unless otherwise specified, the important components involved in this application are purchased from commercially available products, including:
[0035] Fe-Cr-B matrix alloy: the mass percentage of the main components is: Fe: 55%; Cr: 15%;
[0036] B: 3%; C: 0.5%; Manganese: 1%.
[0037] Silicon carbide: purchased from Henan Zhuoxin New Materials Co., Ltd. Specific embodiments
[0039] Example 1
[0040] The secondary casting material of the aluminum piston combustion chamber is prepared by the following method: Fe-Cr-B matrix alloy particles are ball-milled at a ball-milling speed of 400 r / min for 10 h to form a powder;
[0041] 0.5 kg of silicon carbide, 13 kg of Fe-Cr-B matrix alloy powder, 40 kg of aluminum powder, 5 kg of copper powder, 0.4 kg of magnesium powder and 1 kg of nickel powder were weighed respectively, mechanically stirred and mixed, ultrasonically dispersed after mixing, and ultrasonically treated for 20 minutes to obtain a mixed material, wherein the particle size of silicon carbide is 20 μm, the hardness of the Fe-Cr-B matrix alloy is 52 HRC, the purity of Al, Mg, Ni and Cu metal powders is> 98%, and the particle size is 30 μm;
[0042] The mixed material is melted at 900°C with a heating rate of 5°C / min to obtain alloy liquid for secondary pouring.
[0043] Example 2
[0044] The secondary casting material of the aluminum piston combustion chamber is prepared by the following method: Fe-Cr-B matrix alloy particles are ball-milled at a ball-milling speed of 450 r / min for 7 h to form a powder;
[0045] 0.8 kg of silicon carbide, 12 kg of Fe-Cr-B matrix alloy powder, 50 kg of aluminum powder, 4 kg of copper powder, 0.6 kg of magnesium powder and 3 kg of nickel powder were weighed respectively, mechanically stirred and mixed, ultrasonically dispersed after mixing, and ultrasonically treated for 24 minutes to obtain a mixed material, wherein the particle size of silicon carbide is 30 μm, the hardness of the Fe-Cr-B matrix alloy is 54 HRC, the purity of Al, Mg, Ni and Cu metal powders is> 98%, and the particle size is 35 μm;
[0046] The mixed material is melted at 1000°C with a heating rate of 6°C / min to obtain alloy liquid for secondary casting.
[0047] Example 3
[0048] The secondary casting material of the aluminum piston combustion chamber is prepared by the following method: Fe-Cr-B matrix alloy particles are ball-milled at a ball-milling speed of 500 r / min for 8 h to form a powder;
[0049] 1.2 kg of silicon carbide, 10 kg of Fe-Cr-B matrix alloy powder, 70 kg of aluminum powder, 7 kg of copper powder, 0.2 kg of magnesium powder and 0.2 kg of nickel powder were weighed respectively, mechanically stirred and mixed, ultrasonically dispersed after mixing, and ultrasonically treated for 27 minutes to obtain a mixed material, wherein the particle size of silicon carbide is 45 μm, the hardness of the Fe-Cr-B matrix alloy is 58 HRC, the purity of Al, Mg, Ni and Cu metal powders is> 98%, and the particle size is 40 μm;
[0050] The mixed material is melted at 1200°C with a heating rate of 8°C / min to obtain alloy liquid for secondary pouring.
[0051] Example 4
[0052] The secondary casting material of the aluminum piston combustion chamber is prepared by the following method: Fe-Cr-B matrix alloy particles are ball-milled at a ball-milling speed of 400 r / min for 5 h to form a powder;
[0053] 1.5 kg of silicon carbide, 15 kg of Fe-Cr-B matrix alloy powder, 60 kg of aluminum powder, 8 kg of copper powder, 0.8 kg of magnesium powder and 1.5 kg of nickel powder were weighed respectively, and mechanical stirring was performed for mixing, and ultrasonic dispersion was performed after mixing, and ultrasonic treatment was performed for 30 minutes to obtain a mixed material, wherein the particle size of silicon carbide is 60 μm, the hardness of the Fe-Cr-B matrix alloy is 62 HRC, and the purity of Al, Mg, Ni and Cu metal powders is> 98%, and the particle size is 50 μm;
[0054] The mixed material is melted at 900°C with a heating rate of 5°C / min to obtain alloy liquid for secondary pouring.
[0055] Performance Test:
[0056] Tensile strength: According to GB / T4338-2006 "High temperature tensile test method for metal materials".
[0057] Fatigue resistance: According to the national standard "GB / T6398-2017" metal material fatigue crack growth rate test method.
[0058] The secondary casting materials were prepared by using Examples 1-4, and test blocks were prepared according to the above method. The performance of the test blocks was tested. The specific results are shown in Table 1.
[0059]
[0060] Table 1
[0061] According to the test results in Table 1, the tensile strength of the secondary casting materials of Examples 1-4 of the present application can reach more than 400 MPa, and the fatigue crack growth rate is less than 2.5×10 -2 mm / time, the minimum stress concentration factor is 12MPa·m 1 / 2 , all performances are excellent.
[0062] The inventor accidentally discovered that the ratio of the Fe-Cr-B matrix alloy and aluminum powder in the present application has a synergistic effect. The two can further improve the tensile strength and fatigue resistance of the material under high temperature and high pressure with appropriate addition amounts and ratios. The synergistic effect of the Fe-Cr-B matrix alloy and aluminum powder is verified by Examples 5-8 and Comparative Examples 1-2 below;
[0063] Based on Example 2, the casting materials of Examples 5-8 and Comparative Examples 1-2 were designed. Except for the addition of Fe-Cr-B matrix alloy and aluminum powder, the other components and preparation methods remained unchanged. The specific ratio of Fe-Cr-B matrix alloy and aluminum powder is shown in Table 2.
[0064]
[0065] Table 2
[0066] The secondary casting materials prepared in Examples 5-8 and Comparative Examples 1-2 were used to prepare test blocks, and their performance was tested. The specific results are shown in Table 3.
[0067]
[0068]
[0069] Table 3
[0070] From the above performance test, it can be seen from the data in Table 3 that the preferred mass ratio of the aluminum powder of the present application to the Fe-Cr-B matrix alloy is (4.5-6.5):(1.2-1.4), wherein, through Examples 5-6 combined with Example 2, it can be seen from Table 3 that when the ratio of aluminum powder to Fe-Cr-B matrix alloy is 5:(1.2-1.4), the Fe-Cr-B matrix alloy is gradually increased, and the ratio of the Fe-Cr-B matrix alloy is between 1.2-1.4, the tensile strength of the prepared secondary casting material reaches a peak, and the fatigue crack growth rate also reaches the lowest peak, and the stress concentration factor also reaches a minimum value. It can be seen that the Fe-Cr-B matrix alloy has an effect on the tensile strength and fatigue resistance of the secondary casting material. The inventor speculates that the Fe-Cr-B matrix may cause the grain size in the smelt to decrease, causing the stress inside the crystal to increase, thereby causing the hardness of the material to decrease.
[0071] Among them, through the combination of Examples 7-8 and Example 2, it can be seen from Table 3 that when the ratio of aluminum powder to Fe-Cr-B matrix alloy is (4.5-6.5): 1.2, the ratio of aluminum powder is gradually increased. When the ratio of aluminum powder is between 4.5-6.5, the tensile strength reaches a peak, and the fatigue crack growth rate also reaches a minimum peak. The inventor speculates that when aluminum powder contacts the Fe-Cr-B matrix alloy, under high temperature conditions, aluminum is oxidized to Al2O3, and a large amount of heat is released, which promotes the reaction between the Fe-Cr-B matrix alloy and Al2O3. In this case, the Cr and B elements on the surface of the Fe-Cr-B matrix alloy can form a stronger interface bond with Al2O3, thereby improving the performance of the secondary casting material. However, aluminum powder may cause aluminum powder and the Fe-Cr-B matrix alloy to undergo an aluminum oxide reduction reaction and a solid solution reaction. The aluminum oxide reduction reaction will generate a large amount of heat and Al2O3 powder, and the solid solution reaction will form a solid solution of aluminum in the alloy, thereby reducing the performance of the secondary casting material.
[0072] In the present application, based on the above solution, optionally, boron nitride is further added to the secondary casting material, and the mass ratio of silicon carbide to boron nitride is (0.7-1.2):(0.3-0.5).
[0073] Based on Example 6, the casting materials of Examples 9-13 were designed. Except for the changes in the addition amounts of silicon carbide and boron nitride, the other components and the preparation methods remained unchanged. The specific ratios of silicon carbide and boron nitride are shown in Table 4.
[0074] Silicon Carbide Boron Nitride Example 9 0.7 0.5 Example 10 1 0.4 Embodiment 11 1.2 0.3 Example 12 1 0.5 Example 13 1 0.3
[0075] Table 4
[0076] The secondary casting materials prepared in Examples 9-13 were used to prepare test blocks, and their performance was tested. The specific results are shown in Table 5.
[0077]
[0078]
[0079] Table 5
[0080] Through Examples 9-11 in conjunction with Example 6, it can be seen from Table 5 that after compounding silicon carbide and boron nitride and optimizing the ratio, the various properties of the secondary casting material are significantly improved. Silicon carbide-boron nitride has a great influence on the tensile strength and fatigue resistance of the secondary casting material. The inventor speculates that silicon carbide-boron nitride can form a thin film on the surface of the mixed metal powder to prevent the metal powder from oxidizing, so that the metal powders are fully dispersed and mixed evenly. At the same time, under the action of high temperature, silicon carbide-boron nitride can strengthen the interface bonding force between aluminum powder and other metal powders, inhibit the diffusion rate of each component at high temperature, and make the matrix stronger, thereby effectively preventing the segregation phenomenon in the secondary casting material, thereby improving the tensile strength and fatigue resistance.
[0081] Through the combination of Examples 12-13 and Example 10, it can be seen from Table 5 that the ratio of silicon carbide to boron nitride is 1:(0.3-0.5), and the ratio of boron nitride is gradually increased. When the ratio of boron nitride is between 0.3-0.5, the tensile strength and fatigue resistance reach a peak. The inventors speculate that as the ratio of boron nitride increases, an interface reaction will occur between silicon carbide and boron nitride, resulting in an increase in the attraction between silicon carbide and boron nitride particles, thereby causing silicon carbide and boron nitride particles to agglomerate, thereby reducing the tensile strength and fatigue resistance of the secondary casting material.
[0082] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. The secondary casting material of the aluminum piston combustion chamber is characterized by: The invention comprises the following components in parts by weight: 0.5-1.5 parts of silicon carbide, 40-70 parts of aluminum powder, 10-15 parts of Fe-Cr-B matrix alloy, 4-8 parts of copper powder, 0.1-0.8 parts of magnesium powder and 1-3 parts of nickel powder; the mass ratio of the aluminum powder to the Fe-Cr-B matrix alloy is (4.5-6.5):(1.2-1.4); the secondary casting material also comprises boron nitride, and the mass ratio of silicon carbide to boron nitride is (0.7-1.2):(0.3-0.5).
2. The secondary casting material for the aluminum piston combustion chamber according to claim 1, characterized in that: The particle size of the silicon carbide is 20-60 μm.
3. The secondary casting material for the aluminum piston combustion chamber according to claim 1, characterized in that: The hardness of the Fe-Cr-B matrix alloy is 52-62HRC.
4. The secondary casting material for the combustion chamber of an aluminum piston according to claim 1, characterized in that: The purity of the Al, Mg, Ni and Cu metal powders is >98%, and the particle size is 30-50 μm.
5. The method for preparing the secondary casting material of the aluminum piston combustion chamber according to claim 1, characterized in that: The following steps are involved: S1, ball-milling the Fe-Cr-B matrix alloy particles to form powder; S2. According to the formula, silicon carbide, Fe-Cr-B matrix alloy powder, aluminum powder, copper powder, magnesium powder and nickel powder are weighed respectively, mechanically stirred and mixed, and ultrasonically dispersed after mixing to obtain a mixed material; S3, smelting the mixed material at 900-1200° C. to obtain alloy liquid for secondary casting.
6. The method for preparing the secondary casting material of the aluminum piston combustion chamber according to claim 5, characterized in that: The heating rate in step S3 is 5-8°C / min.
7. The method for preparing the secondary casting material of the aluminum piston combustion chamber according to claim 5, characterized in that: The ball milling speed is 400 r / min to 500 r / min, and the ball milling time is 5 to 10 hours.
8. The method for preparing the secondary casting material of the aluminum piston combustion chamber according to claim 5, characterized in that: The ultrasonic treatment time is 20-30 min.
Citation Information
Patent Citations
High-temperature wear-resistance high-strength aluminum alloy composite material for piston and preparation method thereof
CN106756302A
Aluminum matrix composite material having high heat resistance, high rigidity, and low thermal expansion
JP1994212328A